Exploring FlyBase Data Using QuickSearch. Issue 4 (4th April 2023) - Marygold, Steven J.; ,
Abstract: FlyBase (www.flybase.org ) is the primary online database of genetic, genomic, and functional information about Drosophila melanogaster . The long and rich history of Drosophila research, combined with recent surges in genomic‐scale and high‐throughput technologies, means that FlyBase now houses a huge quantity of data. Researchers need to be able to query these data rapidly and intuitively, and the QuickSearch tool has been designed to meet these needs. This tool is conveniently located on the FlyBase homepage and is organized into a series of simple tabbed interfaces that cover the major data and annotation classes within the database. This article describes the functionality of all aspects of the QuickSearch tool. With this knowledge, FlyBase users will be equipped to take full advantage of all QuickSearch features and thereby gain improved access to data relevant to their research. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Using the "Search FlyBase" tab of QuickSearch Basic Protocol 2 : Using the "Data Class" tab of QuickSearch Basic Protocol 3 : Using the "References" tab of QuickSearch Basic Protocol 4 : Using the "Gene Groups" tab of QuickSearch Basic Protocol 5 : Using the "Pathways" tab of QuickSearch Basic Protocol 6 : Using the "GO" tab of QuickSearch Basic Protocol 7 : Using the "Protein Domains" tab of QuickSearch Basic Protocol 8 : Using the "Expression" tab of QuickSearch Basic Protocol 9 : Using the "GAL4 etc" tab of QuickSearch Basic Protocol 10 : Using the "Phenotype" tab of QuickSearch Basic Protocol 11 : Using the "Human Disease" tab of QuickSearch Basic Protocol 12 : Using the "Homologs" tab of QuickSearch Support Protocol 1 : Managing FlyBase hit lists